An Examination of the Factors Related to a Reduction in the Use of Low-Intensity Pulsed Ultrasound (LIPUS). Issue 7 (July 2017) - Uchiyama, Yoshiyasu; Tateiwa, Takaaki; Nakajima, Daisuke; Takatori, Naoki; Watanabe, Masahiko
Abstract : Objective: We examined the factors related to a reduction in the use of low-intensity pulsed ultrasound (LIPUS) for patients at both our hospital and other affiliated institutions. Materials and Methods: Of 350 patients who used LIPUS at our and other affiliated institutions from May 2010 to April 2015, 279 (168 males, 111 females) were evaluated, after excluding mortalities and those with unexplained bone adhesion. Those patients with LIPUS compliance [calculated as: (number of days LIPUS was used/number of days LIPUS was available) × 100] below 80% were defined as the non-compliant group (170 patients), and those patients with a compliance rate of 80% or above were defined as the compliant group (109 patients). Factors related to a reduction in compliance were examined and included duration of use, age, sex, fracture side (right or left), and fracture site. Results: The duration of use was longer in the non-compliant group compared with that in the compliant group (mean ± SD: 160 ± 118 days vs. 126 ± 81 days; P = 0.01), and the mean age was younger in the non-compliant group (42 ± 20 years vs. 50 ± 21 years; P = 0.002). Additionally, there was a higher ratio of females/males in the compliant group (60/49 vs. 120/50; P = 0.008). However, the side of the fracture was not significantly different between the groups ( P = 0.449). Fractures of the forearm were more frequent in the non-compliant group than that in the compliant group (25/170 vs. 7/109; P = 0.003). Discussion: The results suggest that the factors predictive of a reduction in the use of LIPUS are a long period of use, younger age, male gender, and use on fractures of the forearm.